2016
DOI: 10.1002/anie.201511921
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Lewis Pair‐Catalyzed Cycloisomerization of 1,5‐Enynes via a 5‐endo‐dig Cyclization/Protodeborylation Sequence

Abstract: The first frustrated Lewis pair-catalyzed cycloisomerization of a series of 1,5-enynes was developed. The reaction proceeds via the π-activation of the alkyne and subsequent 5-endo-dig cyclization with the adjacent alkene. The presence of PPh3 was of utmost importance on the one hand to prevent side reactions (for example, 1,1-carboboration) and on the other hand for the efficient protodeborylation to achieve the catalytic turnover. The mechanism is explained on the basis of quantum-chemical calculations, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 53 publications
1
33
0
1
Order By: Relevance
“…It is known that cyclopropanes are often readily opened to the respective olefin isomers upon exposure to boron Lewis acids. 10 Therefore, we briefly checked whether the opened isomer of 5b , 2-methyl-1-buten-3-yne, might be involved in this reaction. However, this was not the case.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that cyclopropanes are often readily opened to the respective olefin isomers upon exposure to boron Lewis acids. 10 Therefore, we briefly checked whether the opened isomer of 5b , 2-methyl-1-buten-3-yne, might be involved in this reaction. However, this was not the case.…”
Section: Resultsmentioning
confidence: 99%
“…The application of frustrated Lewis pairs (FLP) has grown immensely since their first report to activate molecular hydrogen (H 2 ) in the absence of transition metals . The development of new FLP‐catalyzed reactions is in the focus of contemporary research resulting in spectacular transformations, for example, the activation of strong C−F bonds, cross‐couplings, or cycloisomerizations . However, the fundamental understanding of FLP reactivity with the aim to establish a structure–reactivity relationship is in its infancies.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Grimme et al. showed that the 1 /PPh 3 FLP catalyzed the 5‐ endo cyclization of 39 to give functionalized indenes 41 ; this was previously reported with a gold catalyst by the group of Sanz (Scheme ) …”
Section: Boron‐based Catalysts For C−c Bond Formationmentioning
confidence: 63%